A comparative study for current transformer dimensioning in overcurrent relay - Bakar, Ab Halim Abu; Zali, S.M.; Tan, Chia Kwang; Illias, Hazlee Azil; Mokhlis, Hazlie (Institute of Electrical Engineers of Japan, 2016)
Dimensioning a current transformer (CT) is one of the most important tasks during the substation planning process. The installation of a correctly specified CT will ensure the integrity of the protection scheme. However, some parameters required for dimensioning a CT can be obtained only after the CT is installed in the substation. Because of the conflicting requirements, utility companies commonly adopt a simplified approach in compensating for the missing parameters. Two other methods for dimensioning CT under the given constraint during the planning stage have also been proposed by several authors. In view of the availability of the three methods of approximating CT specifications, this paper will conduct a comparative study to evaluate their accuracies. The approximated specifications of the CT during the planning stage are compared against those measured from a practical substation. Based on the findings from the comparative studies, the most reliable approach for CT dimensioning during the planning stage is proposed.